2023
DOI: 10.3390/jcm12030762
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Deficits in the Acute Phase of COVID-19: A Review and Meta-Analysis

Abstract: This meta-analysis was conducted to quantify the risk of patients exhibiting cognitive deficits in the acute phase of COVID-19 at the time of the first variants (i.e., before the vaccine) and quantify the potential vulnerability of older patients and those who experienced more severe respiratory symptoms. To this end, we searched the LitCovid and EMBASE platforms for articles, including preprints, and included all studies (n = 48) that featured a measurement of cognition, which encompassed 2233 cases of COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 100 publications
1
5
0
Order By: Relevance
“…For example, a comprehensive examination of 49 largely non-hospitalised COVID-19 patients with an average age of 60 years showed lower scores on mini mental state examination (MMSE) compared to age-matched controls, and 53% were significantly impaired in at least one cognitive domain (attention and executive, memory, or visuospatial) using a more extensive neuropsychological battery 2–3 months after infection [ 28 ]. This accords with a meta-analysis of 24 studies, all using cognitive screening tests, which reported that 52% of patients overall demonstrated acute deficits, and those aged over 59 years fared worse [ 26 ]. However, most of the publications in this analysis focused on hospitalised patients, namely those with more severe manifestations.…”
Section: Cognitive Function In the Acute Phasesupporting
confidence: 77%
See 1 more Smart Citation
“…For example, a comprehensive examination of 49 largely non-hospitalised COVID-19 patients with an average age of 60 years showed lower scores on mini mental state examination (MMSE) compared to age-matched controls, and 53% were significantly impaired in at least one cognitive domain (attention and executive, memory, or visuospatial) using a more extensive neuropsychological battery 2–3 months after infection [ 28 ]. This accords with a meta-analysis of 24 studies, all using cognitive screening tests, which reported that 52% of patients overall demonstrated acute deficits, and those aged over 59 years fared worse [ 26 ]. However, most of the publications in this analysis focused on hospitalised patients, namely those with more severe manifestations.…”
Section: Cognitive Function In the Acute Phasesupporting
confidence: 77%
“…Global, clinical cognitive screening tests were commonly used in the acute phase, namely within 3 months of infection [ 25. , 26. , 27.…”
Section: Cognitive Function In the Acute Phasementioning
confidence: 99%
“…Impairments found using cognitive screening tests, especially in those over 59 years old and hospitalized patients [ 26 , 27 ];…”
Section: Figurementioning
confidence: 99%
“…Although there is much evidence regarding the correlation between COVID-19 and cognitive decline, evaluations and interventions related to cognitive impairment in patients with COVID-19 are currently lacking. Moreover, older adults aged > 55 years tend to be linked to more severe forms of COVID-19 and, therefore, potentially more severe cognitive impairment [ 17 ]. Previous studies have reported that COVID-19 negatively affects cognition, lifestyle, mental health, and quality of life [ 4 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%